Application of Nanosilica from Rice Husk Ash as Iron Metal (Fe) Adsorbent in Textile Wastewater - Rusdianasari Rusdianasari; Muhammad Taufik; Yohandri Bow; Maryam Seyaski Fitria (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
Heavy metals are considered hazardous to health if they accumulate excessively in the body. One way to remove iron metal ions by adsorption process uses adsorbents. In this study, removal of heavy metals such as ferrous metal (Fe) was adsorbed using an adsorbent in the form of nanosilica. Nanosilica is made from rice husk ash where rice husk ash contains 80-90% silica so that it can be utilized as a raw material in nanosilica synthesis. Synthesis of nanosilica was carried out using a solvent in the form of KOH with a variation of 1.5M concentration; 2.5M; 3.0M; 3.5M and 4.5M. The five types of nanosilica were applied to textile waste containing ferrous metal (Fe) with variations in a contact time of 5, 10, 15, 20, and 25 minutes. Waste containing iron metal that has been adsorbed was analyzed by atomic absorption spectrophotometry (AAS) to see the remaining iron content. From the analysis of AAS produced the smallest iron concentration of 0.186 ppm in nanosilica with 1.5 M KOH solvent. Nanosilica with 1.5M KOH solvent was characterized using a Scanning electron microscopy (SEM) -Energy Dispersive X-ray (EDX) tool to obtain a surface morphological size of 0.44 µm with 28.95% SiO2 content.